Possible treatments for arsenic removal in Latin American waters for human consumption - Litter, Marta Irene (2010)
Considering the toxic effects of arsenic, the World Health Organization recommends a maximum concentration of 10 μg L−1 American populations present severe health problems due to consumption of waters with high arsenic contents. Because the physicochemical properties of surface and groundwaters are different from those of other regions of the planet, the problem is still publicly unknown. Methods for arsenic removal suitable to be applied in Latin American waters are here summarized and commented. Conventional technologies (oxidation, coagulationcoprecipitation, adsorption, reverse osmosis, use of ion exchangers) are described, but emphasis is made in emergent decentralized economical methods as the use of inexpensive natural adsorbents, solar light technologies or biological treatments, as essential to palliate the situation in poor, isolated and dispersed populations of Latin American regions. Capsule: low-cost techniques should be urgently investigated to remove arsenic in drinking water in poor disperse rural and urban Latin American populations.